2022
DOI: 10.34133/2022/9802969
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatment Promotes Ubiquitin-Mediated Proteolysis of SARS-CoV-2 RNA Polymerase and Decreases Viral Load

Abstract: Despite extensive efforts, COVID-19 pandemic caused by the SARS-CoV-2 virus is still at large. Vaccination is an effective approach to curb virus spread, but several variants (e.g., delta, delta plus, omicron, and IHU) appear to weaken or possibly escape immune protection. Thus, novel and quickly scalable approaches to restrain SARS-CoV-2 are urgently needed. Multiple evidences showed thermal sensitivity of SARS-CoV-2 and negative correlation between environmental temperature and COVID-19 transmission with unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This result is consistent with an earlier study implicating ZNF598 E3 ligase activity and the ubiquitination of Rps20, but not Rps10, in vaccinia virus replication and the synthesis of vaccinia viral proteins whose encoding mRNAs contain unusual 5’ poly(A) leaders ( DiGiuseppe et al, 2018 ). Interestingly, a recent study showed that mild heat treatment destabilized the RNA-dependent RNA polymerase (also known as Nsp12 protein) encoded by SARS-COV2 virus in a mechanism mediated by ZNF598-dependent ubiquitination of Nsp12 ( Maimaitiyiming et al, 2022 ), suggesting a novel mechanism of action of ZNF598 in cellular response to viral infection and a new way to interfere with SARS-COV2 replication and combat the ongoing COVID-19 epidemic.…”
Section: Translational Regulation and Ribosome-associated Quality Con...mentioning
confidence: 99%
“…This result is consistent with an earlier study implicating ZNF598 E3 ligase activity and the ubiquitination of Rps20, but not Rps10, in vaccinia virus replication and the synthesis of vaccinia viral proteins whose encoding mRNAs contain unusual 5’ poly(A) leaders ( DiGiuseppe et al, 2018 ). Interestingly, a recent study showed that mild heat treatment destabilized the RNA-dependent RNA polymerase (also known as Nsp12 protein) encoded by SARS-COV2 virus in a mechanism mediated by ZNF598-dependent ubiquitination of Nsp12 ( Maimaitiyiming et al, 2022 ), suggesting a novel mechanism of action of ZNF598 in cellular response to viral infection and a new way to interfere with SARS-COV2 replication and combat the ongoing COVID-19 epidemic.…”
Section: Translational Regulation and Ribosome-associated Quality Con...mentioning
confidence: 99%
“…Furthermore, different ubiquitin ligases have been identified as potent restrictors of SARS-CoV-2. Li et al (2023) showed that the E3 ligase RNF5 promotes the ubiquitination and degradation of the viral envelope protein, inhibiting SARS-CoV-2 replication [69,106]. Furthermore, tripartite motif (TRIM) proteins such as TRIM25 and TRIM56, known for their involvement in maintaining cellular proteostasis and preventing protein aggregation in neurodegenerative disorders, also contribute to the defense against COVID-19 through their ubiquitin ligase activity [107,108].…”
Section: Erad/ups-related Antiviral Strategies Against Sars-cov-2mentioning
confidence: 99%
“…being a crucial component of the polymerase (Wang et al, 2020). An investigation has revealed that elevated temperatures can impede the virus by facilitating nsp12 ubiquitination mediated by E3 ubiquitin ligase Zinc Finger Protein 598 (ZNF598), leading to a reduction in the quantity of viral RNA copies and a decrease in the viral concentration (Maimaitiyiming et al, 2022). Additionally, it is widely recognized that Mpro, a kind of 3CLpro, plays a crucial role in the viral replication process due to its ability to cleave viral polyproteins, releasing nsps that initiate subsequent virus transcription.…”
Section: Sars-cov-virus Invasionmentioning
confidence: 99%